PERAN GURU PAI MENGATASI KESULITAN SISWA DALAM LITERASI AL-QUR’AN - Surawan Surawan; Cindy Fatimah (Universitas Islam Sultan Agung, 2021)
This article is motivated by the phenomenon of the students of SMPN Satap-1 Kamipang in the form of difficulties in literacy, namely reading and writing the Qur'an, it is necessary to explore how the role of PAI teachers in overcoming the difficulties of these students. For this reason, this article aims to look at the role of Islamic Religious Education (PAI) teachers in overcoming the difficulties of students in al-Qur'an literacy at the junior high school level. This study uses a descriptive qualitative approach, with data obtained from scientific journal literature, books, and interviews with a PAI teacher and several students of SMPN Satap-1 Kamipang. The data collection technique was carried out by purposive sampling. The results of the study found that the role of PAI teachers was to overcome students' difficulties in al-Qur'an literacy at SMPN Satap-1 Kamipang. Among them are, motivators (providing enthusiasm and motivation), Counselors (providing understanding to students), Observatory (knowing students' abilities in al-Qur'an literacy), facilitators (providing direct guidance), informers (providing information and directives), and evaluator (give an assessment).Keywords: Literacy of the Al-Qur’an, Student Difficulties, The Role of Islamic Education Teachers